Assessing the responses of Sphagnum micro-eukaryotes to climate changes using high throughput sequencing - Reczuga, Monika; Seppey, Christophe Victor William; Mulot, Matthieu; Jassey, Vincent E.J.; Buttler, Alexandre; Slowinska, Sandra; Slowinski, Michal; Lara, Enrique; Lamentowicz, Mariusz; Mitchell, Edward (My University, 2020)
Current projections suggest that climate warming will be accompanied by more frequent and severe drought events. Peatlands store ca. one third of the world’s soil organic carbon. Warming and drought may cause peatlands to become carbon sources through stimulation of microbial activity increasing ecosystem respiration, with positive feedback effect on global warming. Micro-eukaryotes play a key role in the carbon cycle through food web interactions and therefore, alterations in their community structure and diversity may affect ecosystem functioning and could reflect these changes. We assessed the diversity and community composition of Sphagnum-associated eukaryotic microorganisms inhabiting peatlands and their response to experimental drought and warming using high throughput sequencing of environmental DNA. Under drier conditions, micro-eukaryotic diversity decreased, the relative abundance of autotrophs increased and that of osmotrophs (including Fungi and Peronosporomycetes) decreased. Furthermore, we identified climate change indicators that could be used as early indicators of change in peatland microbial communities and ecosystem functioning. The changes we observed indicate a shift towards a more “terrestrial” community in response to drought, in line with observed changes in the functioning of the ecosystem.
Keywords: Wetlands; Protists; Warming; Water table manipulation; Food-web; Biodiversity; Community structure